1985
DOI: 10.1111/j.1600-0722.1985.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscope study of the three‐dimensional extent of Retzius lines in human dental enamel

Abstract: – A method involving carefully planned sectioning and grinding of human maxillary first premolars, allowing enamel structure to be studied with the SEM in more than one plane at the same time, was employed to demonstrate the extent of Retzius lines within the confines of the three‐dimensional enamel cap. It was found that the Retzius lines behaved as could be predicted by the theory stating that the striae represent one‐dimensional cuts of two‐dimensional, curved growth planes. Retzius lines in adjoining plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
9
0
4
Order By: Relevance
“…The SEM technique reveals fewer Retzius lines than light microscopy (Risnes, 1985). Kantorowicz (1904) and Cavanha (1965) reported that Retzius lines were a prominent feature in light-microscopic observations of pearl enamel.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM technique reveals fewer Retzius lines than light microscopy (Risnes, 1985). Kantorowicz (1904) and Cavanha (1965) reported that Retzius lines were a prominent feature in light-microscopic observations of pearl enamel.…”
Section: Discussionmentioning
confidence: 99%
“…5). Andresen lines have been shown to be equivalent to Retzius lines (42), which are equivalent to perikymata (43), and therefore it is the case that internal and external crown and root long-period lines share the same periodicity.…”
Section: Methodsmentioning
confidence: 99%
“…There is no doubt that perikymata are continuous with underlying striae of Retzius [72,73] (fig. 3), but not all striae reach the surface.…”
Section: Perikymatamentioning
confidence: 99%